Philosophia Perennis in the Bosnian Spirit - Kahteran, Nevad (Bulletin of the Nanzan Institute for Religion & Culture, 2006)
As part of a general project to broaden the base of “philosophy” to include more and more of the intellectual traditions of the East, the Nanzan Institute is pleased to reproduce the following essay by Nevad Kahteran, associate professor in Comparative Philosophy and the History of Eastern Philosophy at the University of Sarajevo in Bosnia and Herzegovina. It was composed during a recent stay in Japan as a visiting scholar at Kyoto University under the auspices of the Japan Foundation.